Kajian Faktor Penentu Pengembangan Objek Wisata Pulau Sara Besar di Desa Lirung Kecamatan Lirung Kabupaten Kepulauan Talaud - Taalempungan, Riska; Sindua, Nixon Jefres; Ramadhan, Muhamad Isa; Poli, Ellen Eva; Kapoh, Vidi Feronika (Jurnal Social Science, 2024)
This study aims to examine the development of the Sara Besar Island tourist attraction with a focus on attractions, utilization of nature/environment, the beauty of the beach and underwater, accessibility, and facilities and infrastructure. This study uses a qualitative descriptive method. The study results indicate that the Sara Besar Island tourist attraction, which has a natural panorama and a stretch of white sandy sea, has great potential to be developed. The community expects the government to be able to manage this tourist attraction well. Beach and underwater tourism must be considered and sustainable so that marine biota do not become extinct. Accessibility to this tourist attraction is good, the entrance road is neatly arranged, and vehicle circulation is safe. Facilities and infrastructure still need to be improved so that its appeal increases.